Memaksimalkan Kembali Peran Kepala Sekolah sebagai Supervisor Pendidikan - Muh. Hizbul Muflihin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
This study aims to explore the pivotal role of the school principal in escalating his/her capacity as a supervisor. Supervision constitutes one of the principal’s duties that needs to be carried out for the purpose of supervising, evaluating performance, guiding, and motivating teachers to be able to make improvements, maintain teaching quality, and organize a better learning process. A qualitative descriptive approach was employed in this library research. The findings demonstrate the roles that principals take to maximize their role as a supervisor. Firstly, the principals should be able to understand the nature of supervision. This indicates that this re-understanding aims to enhance the process of supervision and guidance to teachers so as to improve the quality of their performance and teaching processes. Secondly, principals should be able to adapt and adopt various approaches to the implementation of supervision. The application in the supervision approach can be noticed in the exchange of information between principals and teachers, including the quality of learning. Thirdly, school principals should be able to increase human resources. The improvement should be carried out systematically and continuously through professional development. This illustrates that the principals’ role as a supervisor is very essential to promote the professionalism of teachers and educational staff.